Ethynylene-analogues of hemicurcuminoids: Synthesis and ground- and excited properties of their boron difluoride complexes. (June 2017) - Štefane, Bogdan; Požgan, Franc; Kim, Eunsun; Choi, Eunyoung; Ribierre, Jean-Charles; Wu, Jeong Weon; Ponce-Vargas, Miguel; Le Guennic, Boris; Jacquemin, Denis; Canard, Gabriel; Zaborova, Elena; Fages, Frédéric; et al.
Abstract: The synthesis, characterization and (TD)-DFT calculations of the electrochemical and photophysical properties of novel ethynylene-analogues of hemicurcuminoids are described. These dyes are both emissive in solution and in the solid state. While compounds that emit through an efficient charge transfer (CT) state show solvatochromic behaviour associated with low fluorescence quantum yields, those lacking of donor groups show high fluorescence quantum yields of 70–80%, in solution. The latter dyes also present the advantage to emit in the solid state in the visible region with fluorescence quantum yields up to 23%. Their condensed phase spectrum can be bathochromically shifted to the near infrared region (742 nm) by appending a strong donor group. Graphical abstract: Highlights: Synthesis of new fluorophores based on hemicurcuminoid boron difluoride. Photophysical study reveals strong emission of the dyes not containing charge transfer states. Fluorescence properties of dyes in their condensed phase show aggregation induced emission.